IMPLEMENTASI MODEL NCIP DI SEKOLAH DASAR HASIL REGROUPING DI KAWASAN TIMUR INDONESIA - Nur Luthfi Ardhian; Arifin Suking; Besse Marhawati; Avienza Latif; Sutri Atono (As-Sulthan Journal of Education, 2026)
This study aims to evaluate the implementation of the New Culture Integration Process (NCIP) model in elementary schools resulting from regrouping in Gorontalo, focusing on four stages of integration: pre-merger, during-merger, post-merger, and cultural integration. A descriptive quantitative approach was employed involving all elementary schools resulting from regrouping in Gorontalo as the population. Data were collected through questionnaires and analyzed using descriptive statistics with five-category interval criteria. The findings reveal a consistent pattern of improvement across all implementation stages. The pre-merger stage achieved a score of 4.13 (high category) as an initial foundation, although weaknesses were identified in feasibility study (4.03) and benchmarking (3.84) indicators. The during-merger stage increased significantly by 0.15 points to 4.28 (very high category), with main strengths in resource management and leadership. The post-merger stage reached 4.33 (very high category), demonstrating organizational resilience with organizational values and leadership roles as primary contributors. The cultural integration stage maintained a score of 4.33 (very high category), indicating a plateau of excellence where integration quality stabilizes at an optimal level, characterized by sustained commitment, exemplary leadership, multi-level trust, strong togetherness, and efficiency in building communication. These findings validate the NCIP model design that each stage builds foundations for subsequent stages, with effective leadership as a key success factor. Recommendations include strengthening analytical capacity in pre-merger planning, developing sustainable leadership programs, and strategies for embedding culture into daily activities. Future studies may explore the longitudinal dynamics of cultural integration and develop early detection instruments for potential inefficiencies in merger planning.